A educação na abordagem das capacitações - Diniz, Géssica Mathias (2016)
The word education comes from the latin educare meaning "drive out". Education, understood here as the act of educating, it can occur at school, interaction with colleagues or can be developed via the media. Until the nineteenth century, education was a privilege for the few, the intellectual formation was restricted elites and popular classes were indoctrinated in accordance with the interests of the elite. In the twentieth century, the progressive education and postmodern trace other purpose for education, not indoctrination but rather the formation of critical citizens who are able to understand the reality around them and transform it. The functions performed by education, according to the progressive pedagogical thought of Paulo Freire and postmodern and the reports of the UNESCO (2013, 2014) and by the UNDP (2015), forward this study to the analysis of education in space freedom. The Capability Approach crafted by Amartya Sen (1979a, 1985, 2010) focuses on the freedom that the individual must possess to perform the beings and doings it considers of value to your life, having the freedom to expand their set of freedoms. By adopting the Capability Approach as a theoretical framework this paper aims to provide answers the following question: what is the contribution of the Capability Approach in the analysis of the roles (instrumental and intrinsic) of education in the lives of individuals? The main objective of this study was to present education in the Capability Approach and explores the relevance of education not only as a tool for the expansion of human freedom but also as an important resource for their very existence, by allowing the individual to develop their judgment and discernment skills. The theoretical and bibliographic references used allowed to describe various aspects associated with access to education that strengthened the importance of analyzing education through the prism of human freedoms. Education not only improves the social and economic conditions of individuals, but contributes to its formation as a human being, aware of the reality around him, respect human diversity (racial, gender, cultural, religious, etc.), knowledgeable of their rights and duties, opinion leader. Education, formal and informal, makes the free individual to exercise control over your own life and achieve what he considers value for you (positive freedom), not only acts as an instrumental freedom, but rather as an intrinsic freedom by value which has in shaping the individual as a human being (substantive freedom).